A Comparative Study Of Lateral Anal Sphincterotomy Versus Transfissure Sphincterotomy In Cases Of Fissure In Ano (Indian Journal of Applied-Basic Medical Sciences, 2021)
OBJECTIVE The present study is designed to compare the effect of two most commonly used surgical  procedure for anal fissure: Lateral Anal Sphincterotomy and Trans fissure Sphincterotomy with  regards to fissure healing time, pain reduction, cessation of bleeding per rectum post  operatively as well as the complications like flatus and feces incontinence post operatively in  both surgical procedures. METHODOLOGY This hospital based prospective cohort study was undertaken at GCS hospital Ahmedabad  (tertiary care hospital) from March 2019 to December 2019. 50 patients were enrolled in the  study from which 25 patients were randomly assigned to lateral anal sphincterotomy group and  25 were assigned to trans fissure sphincterotomy group. RESULTS Our study establishes that although there is no statistically significant difference in pain  alleviation and relief from bleeding per rectum post operatively in anal fissure between the  Lateral Anal Sphincterotomy and Trans fissure Sphincterotomy, yet the fissure healing is  earlier in Lateral Anal Sphincterotomy than in Trans fissure Sphincterotomy. There is also  slight predominance of flatus incontinence rate in Trans fissure Sphincterotomy group as  compared to Lateral Anal Sphincterotomy. CONCLUSION Thus, we can conclude from over all study that the lateral anal sphincterotomy is far better than  the trans fissure sphincterotomy for the treatment of the fissure in ano by looking at various  perspectives in areas of postoperative outcome.
Keywords: Fissure in ano; lateral anal sphincterotomy; trans fissure sphincterotomy; bleeding per rectum